fMRI studies evaluating central respiratory control in humans - Ciumas, Carolina; Rheims, Sylvain; Ryvlin, Philippe (Frontiers in Neural Circuits, 2022)
A plethora of neural centers in the central nervous system control the fundamental respiratory pattern. This control is ensured by neurons that act as pacemakers and which activity is modulated through chemical control that reacts to any changes in the O2/CO2 balance. Most of the respiratory neural centers are located in the brainstem, but are difficult to localize on magnetic resonance imaging (MRI) due to their small size, lack of visually-detectable borders with neighboured areas, and significant physiological noise hampering detection of its activity with functional MRI (fMRI). Yet, several approaches make it possible to study the normal response to different abnormal stimuli or conditions such as CO2 inhalation, induced hypercapnia, volitional apnea, induced hypoxia etc. This review provides a comprehensive overview of the majority of available studies on central respiratory control in humans.